Discrete-Time Modelling of the Moog Sawtooth Oscillator Waveform. (15th March 2011) - Pekonen Pekonen, Jussi Jussi; Lazzarini Lazzarini, Victor Victor; Timoney Timoney, Joseph Joseph; Kleimola Kleimola, Jari Jari; Välimäki Välimäki, Vesa Vesa
Abstract : Discrete-time modelling strategies of analogue Moog sawtooth oscillator waveforms are presented. Two alternative approaches suitable for real-time implementation are proposed, one modelling the analogue waveform in time domain using phase distortion synthesis and another matching the spectrum of an existing antialiasing sawtooth oscillator to the corresponding analogue spectrum using a first-order IIR post-equalising filter. A parameter estimation procedure for both approaches is explained and performed. Performance evaluation using polynomial fits for the estimated parameters is carried out, and good matches between the model outputs and recorded waveforms are obtained. The best match of the tested algorithms is produced by the phase distortion model and by post-equalising the fourth-order B-spline bandlimited step function sawtooth oscillator.